2021
DOI: 10.1590/1982-0216/202123212120
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between symptoms of attention-deficit/hyperactivity disorder and speech-language-hearing aspects

Abstract: Purpose: to investigate the association of symptoms of inattention and hyperactivity with language development and cognitive, environmental, socioeconomic, and quality of life aspects in children with attention-deficit/hyperactivity disorder. Methods: an observational, analytical, cross-sectional study with a sex-stratified sample of 38 children 7 to 12 years old, diagnosed with attention-deficit/hyperactivity disorder. The assessments approached sociodemographic and environmental aspects, the quality of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
0
0
1
Order By: Relevance
“…The study's goal is to link the indications and symptoms of inattention and hyperactivity in children with attentiondeficit/hyperactivity disorder to language development, and cognitive, environmental, socioeconomic, and subtle lifestyle changes [10]. Researchers found that 6% of children under five and 8% of children under nine had above-threshold scores when utilizing the strengths and problems questionnaire as their primary indicator.…”
Section: Introductionmentioning
confidence: 99%
“…The study's goal is to link the indications and symptoms of inattention and hyperactivity in children with attentiondeficit/hyperactivity disorder to language development, and cognitive, environmental, socioeconomic, and subtle lifestyle changes [10]. Researchers found that 6% of children under five and 8% of children under nine had above-threshold scores when utilizing the strengths and problems questionnaire as their primary indicator.…”
Section: Introductionmentioning
confidence: 99%
“…A consciência fonológica, o acesso ao léxico mental e a memória de trabalho fonológica fazem parte do processamento fonológico, caracterizado pelas operações mentais realizadas com base na estrutura da linguagem oral (MACHADO-NASCIMENTO et al, 2021). No presente estudo, foram encontrados 42,3% de alterações em consciência fonêmica e 34,6% em consciência silábica.…”
Section: Machadounclassified